EFFECTIVE USE OF PROBLEM–BASED SITUATIONS IN ENGLISH LANGUAGE TEACHING - Paizullayev, Yerzhan; Togizbayev, Daulet (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
Problem–based teaching methods are of particular importance for increasing the cognitive interests of students, developing communication skills in a foreign language. Problem–based learning allows students to develop critical thinking, creative abilities, cognition, and activity. The stages of constructing problem situations in teaching English, the importance of the discussion method, as well as the methodology for working with stable phrases are presented with illustrative examples. It has been proven that problem–based learning methods play a special role in increasing the independence and activity of students and the development of intercultural communication.
Keywords: problem–based learning; situation; method; development; activeness; discussion; competence; English